Legal Review Of The Cancellation Of Notary Deeds - Suhario Tanamo Aidi (International Journal For Advanced Research, 2025)
This study examines the legal consequences when a notarial deed is declared null and void or can be revoked by the court, and identifies the factors that lead to this condition. The study uses a normative legal method with a statutory , conceptual, and case (jurisprudential) approach. Primary and secondary legal materials are analyzed descriptively and qualitatively to map the differences between the concepts of ' null and void ' , ' can be revoked ' , and ' not legally enforceable ' , along with their implications for the evidentiary power of authentic deeds. The results of the study indicate that courts in practice more often declare deeds void than 'cancel' notarial deeds. The legal consequences are a decrease in the formal and material evidentiary power of the deed, as well as the possibility of civil liability for the notary if proven negligent in fulfilling the provisions of the Notary Law and the valid requirements for agreements in the Civil Code . Triggering factors that often arise include failure to fulfill the formal requirements for making a deed (reading in the presence of the parties, simultaneous presence and signing, witness identity), defective will (duress or error), failure to fulfill the elements of Article 1320 of the Civil Code, and disputes over the object of the agreement. Jurisprudential review, including Supreme Court Decision No. 1511 K/Pdt/2017, emphasizes the importance of notary caution in verifying the parties and procedural compliance. The implications of the research emphasize strengthening compliance with deed making procedures, documentation of the reading and signing process, and due diligence on documents and the capacity of the parties to minimize the risk of the deed losing its evidentiary power.